The Hidden Advantage of Delegation: Pareto Improvements in a Gift Exchange Game - Charness, Gary; Cobo-Reyes, Ramón; Jiménez, Natalia; Lacomba, Juan A; Lagos, Francisco (American Economic Review, 2012)
This paper analyzes the effect on performance and earnings of delegating the wage choice to employees. Our results show that such delegation significantly increases effort levels. Moreover, we observe a Pareto improvement, as the earnings of both employers and employees increase when employers delegate than when they do not. Interestingly, we also find that the employees' performance under delegation is higher than under nondelegation, even for similar wages. While there is strong evidence that behavior reflects strategic considerations, this result also holds for one-shot interactions. A possible nonstrategic motivation explaining the positive reaction to delegation is a sense of enhanced responsibility. (JEL J31, J33, J41)